Information Technology Asset Security Risk Management at the Secretariat of the Salatiga City DPRD Using ISO 31000 - Margaretha Ayuningtyas; Penidas Fiodinggo Tanaem (Universitas Bina Darma, 2022)
The lack of resources that have an information technology background in handling information technology asset security risks makes it asset management in the Secretariat of the Salatiga City DPRD less optimal. The application of risk management is very necessary, especially in the security of information technology assets in agencies because it can help all existing business process activities in agencies so that they can run well. For this reason, it is necessary to implement information technology asset security risk management using ISO 31000 in these agencies. By implementing the ISO 31000 framework at the Secretariat of the Dprd Kota Salatiga can assist agencies in achieving goals, making decisions, improving performance, and effectively allocating and using resources for risk management. The purpose of this study is to identify, analyze, and handle information technology security risks that exist in the Secretariat of the Salatiga City DPRD. The method used by this research is a qualitative approach, namely case study. The result of this study is that there are 20 possible risks that can interfere with business processes in the Secretariat of the Salatiga City DPRD, including 3 possible high-level risks, 12 possible medium-level risks, and 5 possible low-level risks.